Major depression and psychiatric comorbidity in Turkish children and adolescents with cystic fibrosis - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA; PERDAHLI FİŞ, NEŞE (WILEY, 2019)
Background Many psychological factors contribute to an increased risk of depression in children and adolescents with cystic fibrosis (CF). This study aims to evaluate coexisting psychiatric disorders, perceived social support, and quality of life (QoL) in Turkish children with CF and compare these factors with those of a control group. Methods The study group consisted of 32 children (8-16 years of age) with CF and a group of 33 age- and sex-matched control children. All subjects completed the Children's Depression Inventory (CDI), Screen for Child Anxiety and Related Disorders (SCARED), Social Support Appraisals Scale, and Pediatric Quality of Life Questionnaire. Psychiatric diagnoses were established using the Kiddie Schedule for Affective Disorders and Schizophrenia-Present and Lifetime Version. Results Of the children with CF, 80% of those in the 8 to 11 years age range and 50% of those in the 12 to 17 years age range had at least one psychiatric disorder, that is, 68% of the 33 children with CF had at least one psychiatric disorder. Anxiety disorder (46.8%) and attention deficit and hyperactivity disorder (21.8%) were also common among children with CF. The rates of depression in the CF group and control group were 21.9% and 6.1%, respectively (P > .05). The CF subjects with coexisting depression exhibited higher levels of disease severity, longer periods of hospitalization, and more frequent anxiety disorder. When compared with the control group, the QoL among the Turkish children with CF was lower (P < .05). The CDI and SCARED are relatively sensitive and specific screening tools for depression and anxiety in children with CF. Conclusions Psychiatric disorders were more frequently found in children and adolescents with CF. By examining symptoms of anxiety and depression and by using screening tools, CF patients who exhibit symptoms of psychiatric disorders can be better identified and evaluated.
Keywords: children; cystic fibrosis; depression; psychopathology; QUALITY-OF-LIFE; SOCIAL SUPPORT; HEALTH; ANXIETY; PREVALENCE; DISORDERS; ADHERENCE; SYMPTOMS; ADULTS